Growth, Microstructure, and Mechanical Properties of Co–Cr–Mo Crystal Fibers Fabricated from the Melt by Unidirectional Solidification. Issue 10 (23rd June 2021) - Yokota, Yuui; Nihei, Takayuki; Abe, Shoki; Yoshikawa, Akira
Abstract : Many complicated forming processes are required to fabricate thin wires of Co–Cr–Mo (CCM) biomedical materials due to the poor workability of these materials. A novel fabrication technique for CCM crystal fibers is developed by unidirectional solidification directly from the melt using the alloy‐micro‐pulling‐down (A‐μ‐PD) method. Compared with conventional methods, the proposed technique is an innovative fabrication method for CCM alloy fibers and is characterized by low cost, time saving, and low loading. In addition, the proposed method shows potential for further thinning of fibers. At growth rates of 0.1 and 0.3 mm min −1, CCM single‐crystal fibers composed of the ε‐phase with a hexagonal close‐packed (hcp) structure (hcp ε‐phase) can be fabricated. The hcp‐ε‐phase CCM crystal fibers exhibit considerably improved strain because of the slipping line in the hcp structure. Moreover, the γ‐phase with an fcc structure (fcc γ‐phase) appears in the hcp‐ε‐phase at growth rates greater than 0.5 mm min −1, and the ratio of the fcc γ‐phase in the CCM crystal fibers systematically increases with an increase in the cooling rate. The results reveal that the growth rate in the A‐μ‐PD method has a notable effect on the fabrication of single‐ or polycrystalline CCM fibers. Abstract : A novel fabrication technique for Co–Cr–Mo crystal fibers is developed by unidirectional solidification directly from the melt method. The growth rate has a notable effect on the fabrication of single‐ or polycrystalline fibers. The face‐centered cubic (fcc) γ‐phase appears in the hexagonal close‐packed ε‐phase at growth rates greater than 0.5 mm min −1, and the fcc‐γ‐phase ratio increases as the cooling rate increases.